О перестройке мышления: (диалог с читателями) (В. Л. Алтухов) - Алтухов Валерий Лаврович (1989)
Экземпляры: КХ (20110628) / Инвентарный номер: 0281919 / Цена: 0.15 / Сис.шифр: 15.56 / Авт.знак: А 52 / ГРНТИ: 02 / ББК: 60.028